Risk assessment process of hazards in construction sites - Sarpin, Norliana (2006)
Recently the issue of occupational safety and health have attract the attention of many parties in the construction industry. The number of accident occurrence in construction site have been regard as high if compared to other industries. One of the main cause of accident in many construction sites is hazards, therefore an effective risk assessment process of hazards has the potential to overcome the problem. This study is carried out to determine the process of risk assessment of hazards currently applied in construction sites in Malaysia. The study also aim to proposed a guideline that can be used by the construction personnel in order to improve the implementation of risk assessment of hazards. A framework of the current applied risk assessment process of hazards have been developed from the combination of the result of interview session carried out by the author with ten construction companies. The study found that the major risk assessment process of hazards in construction sites listed were approved by the respondent as ‘high application’ and ‘medium application’. Based on the study analysis, a guideline have been proposed and it is expected by this guideline, construction personnel will be able to implement the risk assessment process of hazards effectively in construction sites in Malaysia.